2020
DOI: 10.3390/cancers12102937
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Orthotopic Patient-Derived Xenograft Model of Radiation-Induced Glioma Following Medulloblastoma

Abstract: Radiation-induced glioma (RIG) is a highly aggressive brain cancer arising as a consequence of radiation therapy. We report a case of RIG that arose in the brain stem following treatment for paediatric medulloblastoma, and the development and characterisation of a matched orthotopic patient-derived xenograft (PDX) model (TK-RIG915). Patient and PDX tumours were analysed using DNA methylation profiling, whole genome sequencing (WGS) and RNA sequencing. While initially thought to be a diffuse intrinsic pontine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 78 publications
(154 reference statements)
0
12
0
Order By: Relevance
“… 57–59 A small cytogenetic study of 3 RIGs reported extremely complex karyotypes 18 ; however, few studies have extensively examined broad chromosomal gains or losses in cranial RIGs. Paugh et al 33 performed the largest analysis to date examining 10 RIG samples, to which we have added seven more cases here 34 , 40 , 43 , 49 ( Figure 3 and Supplementary Tables 2 and 3 ). Overall, the most frequent copy number changes observed in RIGs were loss of 13q (observed in 59% of samples reported), gain of 1q (53%), and loss of 1p (47%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 57–59 A small cytogenetic study of 3 RIGs reported extremely complex karyotypes 18 ; however, few studies have extensively examined broad chromosomal gains or losses in cranial RIGs. Paugh et al 33 performed the largest analysis to date examining 10 RIG samples, to which we have added seven more cases here 34 , 40 , 43 , 49 ( Figure 3 and Supplementary Tables 2 and 3 ). Overall, the most frequent copy number changes observed in RIGs were loss of 13q (observed in 59% of samples reported), gain of 1q (53%), and loss of 1p (47%).…”
Section: Resultsmentioning
confidence: 99%
“…Blue indicates loss and red indicates gain of chromosomal arms, with percentages of cases reporting gain or loss for each arm shown. 33 , 34 , 40 , 43 , 49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our understanding of the molecular pathogenesis of these diseases has improved dramatically in the last three decades, this knowledge has not translated to increased patient survival. Amongst survivors, current treatments can cause debilitating side effects, including untreatable secondary malignancies [ 13 ], cognitive dysfunction, cardiotoxicity, myelosuppression, renal toxicity, and endocrine problems [ 14 ]. Therefore, improved clinical outcomes are dependent on the identification of efficacious therapies that not only increase survival but reduce treatment-related side effects.…”
Section: Introductionmentioning
confidence: 99%
“…This small collection of six original research papers and two review articles in the Special Issue “Rare Childhood Malignancy” highlights the diversity and importance of empirical research into childhood malignancy, a theme that underpins the significant advances that have been made in treating the diseases that constitute cancers in children. These articles cover significant themes in childhood cancer research and include biological studies on the role of MYCN in poor prognosis Wilms’ tumor [ 1 ] and the mTOR complexes in rhabdomyosarcoma [ 2 ]; studies exploring biologically based treatments in ependymoma [ 3 ] and osteosarcoma [ 4 ]; a comprehensive description of a novel orthotopic model for radiation-induced glioma which will be invaluable for preclinical testing [ 5 ]; and two comprehensive review articles on leukemias. One review describes recently identified rearrangements of DUX4 with IGH in childhood B-cell acute lymphoblastic leukemia (ALL) and the diagnostic challenges associated with identifying the rearrangement [ 6 ], and the second proposes that infant acute myeloid leukemia (AML) is a biologically and clinically distinct entity from AML in older children [ 7 ].…”
mentioning
confidence: 99%